INCREASING THE INNOVATIVE BEHAVIOR OF CREATIVE ECONOMY ACTORS IN THE CRAFT SUB-SECTOR IN CIAMIS REGENCY THROUGH SELF-EFFICACY, KNOWLEDGE SHARING AND ORGANIZATIONAL CLIMATE - Tinia, Andini Grace; Kader, Mukhtar Abdul; Malik, Rifki Abdul; Athifah, Anis Azzah; Lestari, Sri (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
Creative Economy (Ekraf) is one of the sectors that is expected to be able to become a new, sustainable force in the national economy and emphasizes adding value to a product or service through human thinking and creativity. Craft products are the sub-sector that is included in the three largest contributors to National Gross Domestic Product in Indonesia. Likewise in Ciamis Regency, this sub-sector is the second leading sub-sector in increasing Original Regional Income. However, creative and creative activities in Ciamis Regency lack the ability to produce, introduce and implement new and unique crafts or products. Meanwhile, creative and creative actors really need innovative behavior to increase business success and survive in tight business competition in the era of a dynamic business world. The aim of this research is to determine the determination of self-efficacy, knowledge sharing and organizational climate towards increasing innovative behavior as well as the role of the Creative Economy Community in increasing innovative behavior in the craft sub-sector in Ciamis Regency. The method used is a mixed method with an explanatory sequential research design. The research results provide an illustration that self-efficacy, knowledge sharing and organizational climate, both partially and simultaneously, have an influence in increasing innovative behavior. The variable that most influences innovative behavior is organizational climate. Qualitatively, the Creative Economy Community (Komenkraf) in the Crafts Sub-Sector in Ciamis Regency has an important role in optimizing self-efficacy, sharing knowledge and organizational climate as an effort to increase the innovative behavior of creative economy actors in the crafts sub-sector in Ciamis Regency.